Qatar’s Rising International Influence: A Case of Soft Power? - Felsch, Maximilian (Conjuntura internacional, 2016)
The Arab uprisings have changed the regional order of the Arab world. As traditional leading powers likeIraq,SyriaandEgypthave lost influence in theMiddle Eastdue to internal security issues and economic difficulties, a few states were able to take advantage of the recent regional turmoil. Seemingly, the mini-state Qatar has managed to benefit from the uprisings more than any other Arab state. Many IR authors explain this phenomenon with the concept of soft power. This paper tests systematically the validity of the soft power argument by examining three “soft power resources” as defined by Joseph Nye: culture, political values, and foreign policies. It is argued that the soft power concept fails in all three aspects to grasp the nature of Qatar’s regional and international influence. Instead, it is suggested to consider Qatar’s ‘hard power’ potentials which define more accurately the actual international influence of the Gulf state.